PENGATURAN PEMBERIAN RESTITUSI DALAM SUATU TINDAK PIDANA PEMBUNUHAN (STUDI PUTUSAN NOMOR 22-K/PMT-II/AD/II/2022) - Rahmawati, Anissa; Yudianto, Otto (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Providing a justice or legal protection for victims of criminal acts is a form of right owned by the victim and the victim's family which can be called the right of restitution, which aims to alleviate suffering and losses caused by a crime. This study aims to determine the importance of granting restitution in a crime of murder. In Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims (UU PSK), it is a concrete form that the Indonesian state supports protecting and providing justice for victims of a crime, for state accountability to the people. As for the processes or phases pertaining to the application for the awarding of rights to compensation and rights to restitution by victims, their families, or their proxies via the Witness and Victim Protection Agency (LPSK), they have the right to petition to court. Procedures for Completing Applications and Granting Restitution and Compensation to Crime Victims, as outlined in Supreme Court Regulation (Perma) No. 1 of 2022. The Criminal Procedure Code (KUHAP) in Article 98 paragraph (1) regulates the merger of cases for compensation. This writing finds the fact that in criminal justice in Indonesia it is still rarely applied by judges in deciding cases of merging compensation claims and in granting restitution to victims of criminal acts which is a form of state responsibility regarding effective protection of human rights (HAM) for victims. However, related to this, in practice, in the provision of restitution, there is still a lack of supervision by the LPSK towards victims after receiving restitution, because the available data is inadequate, as well as a lack of Human Resources (HR) and the lack of a supporting budget in granting restitution.